Hypertonic disease and its involvement in the class of diseases of the circulatory system: epidemiological situation in Ukraine - V.V. Ruden` (Danylo Halytsky Lviv National Medical University, 2020)
Aim. A substantiation by the types of morbidity of biostatistic tendencies in the development of hypertonic disease and its involvement in the existing pathologies of the class of diseases of the circulatory system among the population of Ukraine.